CHEMICAL STABILITY OF ANION EXCHANGE MATERIALS BASED ON POLYVINYL CHLORIDE (Scientific journal of the Fergana State University, 2024)
On an industrial scale, mechanical engineering materials are required to have different physico-chemical properties depending on the field of application, technological processes and the task they perform. Ion-exchange materials are used in hydrometallurgical industry in highly aggressive environments, where ion-exchange materials are mainly required for high chemical and thermal stability, while in other industries, ion-exchange materials are used in high-pressure water flow environments to be mechanically strong, to a certain specific volume and other properties are required. In our discussion below, information is given about the important chemical stability of polyvinyl chloride (PVC)-based anion exchange material.